Let's simplify the original expression step by step:
-
Evaluate \( 7^0 \): \[ 7^0 = 1 \]
-
Evaluate \( (-29)^0 \): \[ (-29)^0 = 1 \]
Now, plug these values back into the expression:
\[ \frac{1}{2}(9 - 1) + 1 \]
This simplifies to:
\[ \frac{1}{2}(8) + 1 = 4 + 1 = 5 \]
Now, let's analyze the answer choices:
A. \( \frac{1}{2}(9 - 0) + 0 \)
Simplifying: \[ \frac{1}{2}(9) + 0 = \frac{9}{2} + 0 = 4.5 \quad \text{(not equal to 5)} \]
B. \( \frac{1}{2}(9 - 1) + 1 \)
Simplifying: \[ \frac{1}{2}(8) + 1 = 4 + 1 = 5 \quad \text{(equal to 5)} \]
C. \( \frac{1}{2}(9 - 1) - 1 \)
Simplifying: \[ \frac{1}{2}(8) - 1 = 4 - 1 = 3 \quad \text{(not equal to 5)} \]
D. \( \frac{1}{2}(2) + 1 \)
Simplifying: \[ 1 + 1 = 2 \quad \text{(not equal to 5)} \]
Therefore, the equivalent expression to the original expression is B: \( \frac{1}{2}(9 - 1) + 1 \).